Due diligence and criminal policy models in the fight against contemporary forms of slavery - García Sedano, Tania (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In the last years there have been normative initiatives that impose managerial obligations supported on the principle of due diligence, fundamentally on the area of global supply chains, in order to prevent the existence of contemporary forms of slavery. This paper is a contribution from the area of international law, the European law and the comparative law to the different models of implementation of the due diligence principle in global supply chains. Our aim is to diagnose which proposals are the most appropriated.